Demonstration of infectious salmon anaemia (ISA) viral antigens in cell cultures and tissue sections - Falk, K; Dannevig, B H (Veterinary research (Paris), 1995)
Rabbit polyclonal antibodies and mouse monoclonal antibodies (MAb) directed against infectious salmon anaemia virus (ISAV) were produced using a virus prepared in a newly established cell line culture developed from Atlantic salmon head kidney (SHK-1) cells. These antibodies were used to establish an indirect fluorescent antibody test for the detection of viral antigens in cell cultures and tissue cryosections. Specific fluorescence was detected in ISAV-infected cell cultures using rabbit polyclonal and MAb. One selected MAb produced specific staining for ISAV in the tissue sections from all the examined organs of ISAV-infected Atlantic salmon 20 d post infection. Fluorescence was mainly found in the endothelial cells and in single cells scattered throughout the parenchyma of the organs.